Ambulatory Heart Rate Variability in Schizophrenia or Depression: Impact of Anticholinergic Burden and Other Factors. Issue 2 (March 2021) - Bengtsson, Johan; Olsson, Erik; Igelström, Helena; Persson, Jonas; Bodén, Robert
Abstract: Background: Heart rate variability (HRV) has been found reduced in patients with schizophrenia and depression. However, there is a lack of knowledge on how demographic, lifestyle, and pharmacological factors contribute to the reduction in HRV in these patients. Methods: We recruited 37 patients with schizophrenia, 43 patients with unipolar depression, and 64 healthy controls. A combined chest-worn HRV and accelerometer device was used in an ambulatory measurement. Age, sex, anticholinergic burden of medication, nicotine use, body mass index, and ongoing physical activity were assessed in multiple regression models regarding their influence on HRV, measured as the standard deviation of all the RR intervals (SDNN). Results: In the fully adjusted model, schizophrenia ( β = −0.23, P = 0.019), depression ( β = −0.18, P = 0.028), age ( β = −0.34, P < 0.000), ongoing physical activity ( β = −0.23, P = 0.001), and anticholinergic burden ( β = −0.19, P = 0.025) influenced SDNN negatively. Sex, nicotine use, and BMI had negligible effects on SDNN. Conclusions: We show for the first time that a quantified score of anticholinergic burden of medication has a negative relationship to HRV in patients with schizophrenia or depression, but that the diagnoses themselves still exhibit an effect on HRV.